Andean identity mutation: Rites and conceptions of divinity - Irarrazaval, Diego (1988)
In the effervescent Andean space, the iconography seems very persistent; human beings are born and die, but the gods remain. There is some truth in this statement. However, they also highlight modifications in representations of the divinity. These mutations are combined with changes in the Andean way of being and self-understanding; These are changes that occur along with the clash between the Andean world and invading cultures. In the following pages we do not concern ourselves with the exchange between the Andean population, Quechua and Aymara and Mestizo, with their maternal divinity. It is an exchange between humans and a divine presence, a give-receive exchange that shows new directions in the ancient Andean identity.